English education for student in globalization era: teacher´s perspective in Jabodetabek - PURNAMA, S.; NASUTION, H.; YANHAR, M.; RISWANTO, R.; HARTINAH, S.; FITRI, S. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study examines the perspectives of English teachers in the Jabodetabek area on improving the English proficiency of students in the region. The data used in this study are data collected through a questionnaire answered by 201 English teachers in the Jabodetabek area. The analysis shows that more than 50% of teachers stated that they strongly agree on five components: namely improving teacher quality (76.1%), the role and guidance of parents (63.2 %), providing motivation to students (62.2%), innovative learning methods and supporting tools (61.7%), and the support of all parties in their application in the school environment (58.2%).RESUMEN Este estudio examina las perspectivas de los profesores de inglés en el área de Jabodetabek. Los datos utilizados en este estudio son datos recopilados a través de un cuestionario contestado por 201 profesores de inglés en el área de Jabodetabek. El análisis muestra que más del 50% de los docentes declararon estar de acuerdo en cinco componentes: mejorar la calidad del docente (76.1%), orientación de los padres (63.2%), proporcionar motivación a los estudiantes (62.2%), métodos de aprendizaje innovadores (61.7%) y el apoyo de todas las partes en su aplicación en el entorno escolar (58.2%).